Kratek oris razvoja telesne vzgoje na Danskem, v Nemčiji, Avstriji in Sloveniji - Čuk, Ivan (Šport (Ljubljana), 2022)
The article briefly presents the development characteristics of physical education in four countries, Denmark, Germany, Austria and Slovenia. The selected countries are comparable to Slovenia in terms of knowledge achievements in international research (OECD PISA, etc.), they are recognized for their more visible achievements in the field of modern, sustainable design of school space, and they have had recent changes in the field of education (for primary school education), with the field of curriculum design space (architecture of school buildings). All selected countries are characterized by the fact that physical culture activities were first carried out by associations. when the authorities realized the importance of physical exercise, they also made it a compulsory subject in school for the education of children and youth. It is interesting that only in Denmark did they first have properly trained teachers, and only then did they introduce physical education into the school environment. All the others first set up the subject in the school and then trained the staff who were to run the subject. The Danes also very soon took care of suitable training facilities, in Austria and Germany much later, and in Slovenia it has only been devoted to this for the last fifty years. In recent history, only Denmark did not have a totalitarian state structure that glorified state ideology (Nazism, Communism), and perhaps that is precisely why today‘s Denmark is a leader and unburdened for new ideas in the school space.
Keywords: Avstrija; Danska; društva; Nemčija; razvoj; Slovenija; šole; šport; športna vzgoja; zgodovina